Kewenangan Pengadilan Negeri Jakarta Pusat Dalam Pembatalan Putusan Arbitrase Di Janewa Swiss (Studi Kasus PT. Pertamina dan PT. PLN melawan Karaha Bodas Company) - Ircham Suryo Nugroho (Lex Renaissance, 2020)
This research examines how the competence/authority of the Central Jakarta District Court in rejecting the arbitration award in Geneva, Switzerland which is final, binding and enforceable in resolving business disputes of PT. Pertamina and PT. PLN against Karaha Bodas Company. This paper uses normative legal research. The result of this research is that international arbitration decisions are final and binding on the parties. Two legal remedies may still be made against this decision, namely the rejection and cancellation of the implementation of foreign arbitration. The emergence of two legal remedies for annulment of the Geneva arbitration award in both the Swiss Federal Court and the Central Jakarta District Court has caused a lot of debate on which court is authorized to annul the Geneva arbitration award. With the appointment of Geneva as the place of arbitration (the arbitration seat) and the law underlying the arbitration dispute settlement (Lex Arbitri), the Swiss Federal Court has the authority to annul the Geneva arbitration award. Thus, the Central Jakarta District Court has no competence to reject the Geneva arbitration award.